Cultural Identity and Intertextual Discourse: A Study of Paper Menagerie by Ken Liu - Rouabhia, Ridha (Indonesian Journal of English Language Studies (IJELS), 2024)
This study investigates the intricate interplay between intertextuality and discourse in Ken Liu’s evocative short story Paper Menagerie, focusing on cultural identity negotiation and heritage language dynamics. Through qualitative literary analysis involving multiple close readings, thematic coding, comparative contextualization, and detailed interpretation, the interplay between Liu’s masterful integration of multifaceted cultural allusions and the discourse patterns surrounding generational language divides and struggles with self-concept is examined. The analysis reveals how Liu adeptly employs intertextuality through origins, Qingming festivities, and other symbols to create resonance and authenticity in exploring assimilationist tensions, while patterns in the text reinforce acculturative pressures and resulting linguistic barriers faced by immigrants. Ultimately, these layers synergize to reflect deeply on the preservation of identity tensions. As with textual analysis, subjective interpretive constraints persist, limiting generalizability. Further exploration through intertextual threads in Liu’s broader writings could enrich the understanding of his versatile identity while revealing philosophical evolution. The intricate symbiosis between intertextuality and discourse breathes life into this narrative, crystallizing universally relatable experiences through a culturally specific lens. While bittersweet, Liu’s artistry is a poignant reminder that interweaving past and present fosters empathy across paper menageries.